Microwave-assisted synthesis and characterization of zinc oxide micropowder - Pusit Pookmanee (2018)
Zinc oxide micropowder was synthesized by a microwave-assisted method. Zinc nitrate and ammonium hydroxide were used as the starting precursors with the mole ratio of 1:1. The white precipitated powder was formed after adding ammonium hydroxide until the pH of final solution was 9 and treated with the microwave radiation power at 1000 Watt for 2-6 min. The phase of zinc oxide micropowder was examined by X-ray diffraction (XRD). A single phase of hexagonal structure was obtained. The morphology and chemical composition of zinc oxide micropowder were investigated by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The particle was plate-like in shape with the range of particle size of 0.1-0.5 μm. The elemental composition of zinc oxide showed the characteristic X-ray energy value as follows: zinc of L α = 1.012 keV, Kα = 8.630 keV and K β = 9.570 keV and oxygen of Kα = 0.525 keV, respectively. © (2010) Trans Tech Publications.